Identifying Prognostic Factors for Drug-Resistant Epilepsy in Children with Cerebral Palsy - Román, Cinthya Carolina Avalos; Rivera, Sofía Lucila Rodríguez (British Journal of Healthcare and Medical Research, 2026)
Background and purpose: Drug-resistant epilepsy is a common and disabling complication in children with cerebral palsy (CP). This study aimed to analyze the relationship between neurological, functional, and perinatal factors and the development of drug-resistant epilepsy in pediatric patients with CP to determine prognostic factors and improve medical management. Methods: We compared three groups of patients with cerebral palsy: those with drug-resistant epilepsy, those with drug-sensitive epilepsy, and those without epilepsy. Clinical variables, perinatal history, characteristics of seizure onset, neuroimaging findings, functional scales (GMFCS, MACS), and comorbidities were collected. Associations were evaluated using appropriate statistical tests, including Fisher's exact test, multiple logistic regression, and inferential statistics in Epi Info™ version 7.2. Results: We studied 80 patients. Drug-resistant epilepsy was present in 49 (61%) of the participants. It was significantly associated with quadriplegic motor involvement (p=0.04), early seizure onset (p=0.03), and corticosubcortical atrophy on neuroimaging (20%, n=16). The need for gastrostomy (p=0.03) and the use of dual therapy (p=0.06) or polytherapy (p=0.008) were also strongly related to drug resistance. Conclusions: Drug-resistant epilepsy in children with CP is strongly linked to markers of severe neurological compromise and early epileptic manifestations, rather than to isolated perinatal complications. Early identification of high-risk profiles may guide timely diagnostic and therapeutic strategies to improve clinical outcomes.